Watch out for the darkness - Müller, Richard Morgan (Revista Letras Raras, 2023)
DOI: https://dx.doi.org/10.35572/rlr.v1i9.1677 Watch out for the darkness. Don't let her erode you. Warm your life with passion and let this be your fuel.